A modern view on the role of single nucleotide polymorphism of human genes in the formation of unfavorable consequences of the new coronavirus disease (COVID-19) - Riabokon, Yu. Yu.; Huseynov, E. M.; Kalashnyk, K. V.; Рябоконь, Юрій Юрійович; Гусейнов, Е. М.; Калашник, Кирило Вадимович (Запорізький державний медикофармацевтичний університет, 2024)
Aim – to analyze the current literature on the role of single nucleotide polymorphism (SNP) of human genes in shaping the clinical course of the new coronavirus disease (COVID-19). Results. Based on the results of the analysis and synthesis of the current literature on the role of SNP in shaping the clinical course and outcome of COVID-19, the clinical and prognostic significance of SNP of genes encoding receptors responsible for the penetration of SARS-CoV-2 into target cells has been demonstrated. The presence of the D-allele of the ACE gene (DD and ID genotypes) is associated with the highest risk of severe COVID-19, which makes it possible to offer it as an informative prognostic marker of COVID-19 severity. SNP of the TMPRSS2 co-receptor gene, known as the androgen responsive gene, at certain loci is prognostically important, as it leads to an increase in TMPRSS2 expression in men, which promotes virus fusion with the target cell membrane and has an unfavorable effect on the course of COVID-19 in men. The data accumulated in the current literature on the clinical and prognostic value of SNP host genes encoding the immune response has also been analyzed. The role of HLA SNP genes, genes encoding innate immunity factors (TLR), as well as genes encoding pro-inflammatory cytokines (IL-6, TNF-α, etc.) and acute-phase inflammatory components (CRP) in the development of severe COVID-19 and the risk of death has been demonstrated. Attention has been paid to the determined role of SNP in the ACE gene in the development of pulmonary embolism in patients with severe COVID-19. The article has analyzed publications on the SNP role of host genes in the development of clinical events that are currently interpreted as long COVID. The prognostic role of the IL-10 gene SNP and its receptor gene in the formation of long-term consequences of the new coronavirus infection has been demonstrated. Мета роботи – проаналізувати відомості сучасної наукової літератури щодо ролі однонуклеотидного поліморфізму (ОП) генів людини у формуванні особливостей клінічного перебігу нової коронавірусної хвороби (COVID-19). Результати. У результаті аналізу й узагальнення відомостей фахової літератури щодо ролі ОП генів господаря у формуванні особливостей клінічного перебігу та наслідків COVID-19 показано клініко-прогностичне значення ОП генів, що кодують рецептори, відповідальні за потрапляння SARS-CoV-2 до клітин-мішеней. Якщо виявлено D-алель гена ACE (генотипи DD і ID), ризик розвитку тяжкого перебігу COVID-19 найвищий. Отже, є підстави визначити його як інформативний прогностичний маркер тяжкості COVID-19. ОП гена ко-рецептора TMPRSS2, відомий як андрогенний реактивний ген, у певних локусах має прогностичне значення, оскільки призводить до збільшення експресії TMPRSS2 у чоловіків, а отже спричиняє злиття вірусу з мембраною клітини-мішені та, відповідно, має несприятливий вплив на перебіг COVID-19 саме в чоловіків. Проаналізовано також відомості наукової літератури щодо клініко-прогностичного значення ОП генів господаря, що кодують імунну відповідь. Показано роль ОП генів системи HLA, генів, що кодують фактори вродженого імунітету (TLR), а також генів, які кодують прозапальні цитокіни (IL-6, TNF-α тощо) та гострофазові компоненти запалення (CRP) у розвитку тяжкого перебігу COVID-19 та ризику летального наслідку. Описано роль ОП поліморфізму гена ACE у розвитку тромбоемболії легеневої артерії у хворих із тяжким перебігом COVID-19. Вивчили дані щодо ролі ОП генів господаря в розвитку клінічних подій, що визначають нині як long-COVID. Описано прогностичну роль ОП гена IL-10 та гена його рецептора в формуванні віддалених наслідків нової коронавірусної інфекції.
Сучасний погляд на роль однонуклеотидного поліморфізму генів людини у формуванні особливостей клінічного перебігу та наслідків нової коронавірусної хвороби (COVID-19)
Riabokon Yu. Yu. - ORCID ID: 0000-0002-2273-8511; Kalashnyk K. V. - ORCID ID: 0000-0002-4532-8953.
Keywords: coronavirus disease; COVID-19; viral infection; single nucleotide polymorphism; clinic; diagnosis; prognosis; коронавірусна хвороба; вірусна інфекція; однонуклеотидний поліморфізм; клініка; діагностика; прогноз